The Social Construction of Quality in Agri-food Localized Systems (SYAL): The Case of the Montpeyroux Wine Arrangement, France - Mascarenhas, Gilberto; Touzard, Jean-Marc (The International Journal of Sociology of Agriculture and Food, 2018)
The approach based on localized agri-food systems (SYAL, from the French acronym) has brought about new perspectives for analysis of local productive arrangements, complementing and expanding the theoretical background of clusters and industrial districts. In addressing physical, institutional, cultural and relational factors, SYAL’s approach has enabled a more dynamic view of the processes underlying the creation, resilience and evolution of these arrangements. However, studies on this topic have only focused on some of these factors. This article aims to analyse how these factors interplay and are integrated into the consolidation of productive arrangements focused on improving the quality of local products. To that end, a case study was conducted in a wine arrangement in Montpeyroux, Southern France, which found synergies, complementarities and a reinforcement process involving these factors in the genesis and configuration of the arrangement, thus showing that methodologies that consider them in an integrated way can provide a better understanding of these arrangements in general and further strengthen SYAL assumptions.